Tails of Cross-Channel Comets: From Acclaim to Obscurity - Demers, Patricia (Renaissance and Reformation / Renaissance et Réforme, 2020)
This article explores the diverse materialities of texts created by three female luminaries that expand our understanding of translation and transformation in early modern Europe. Lady Anne Cooke Bacon’s translation of Bishop Jewel’s Apologia was praised as the official text of the Elizabethan Settlement and printed without change for the edification of both English readers and Continental sceptics. Yet despite its centrality in the vitriolic controversy between Jewel and Louvain Romanist Thomas Harding, within a generation Bacon’s name disappeared. Bilingual calligrapher and miniaturist Esther Inglis prepared and presented stunning manuscript gift books, often including self-portraits, to patrons on both sides of the Channel. Her artisanal expertise emulated and often outdid the typographic variety of the printed text. Scholarly and lionized participant in the Neo-Latin Republic of Letters, Anna Maria van Schurman, whose landmark Dissertatio was translated as The Learned Maid, scandalized her conservative Calvinist supporters by embracing Labadism and praising its simple ways in her autobiography Eukleria. These three early modern women, distinct in temperament, time, and social status, are the subject of this exploration, which seeks to understand the dynamics and fluctuations of cross-Channel transmission and the role played by the Channel divide or bridge in creating a brief notoriety soon to be followed by obscurity.